Quantitation and physiological characterization of angiogenic vessels in mice: effect of basic fibroblast growth factor, vascular endothelial growth factor/vascular permeability factor, and host microenvironment. - Dellian, M. (1996)
A prerequisite for the development of novel angiogenic and anti-angiogenic agents is the availability of routine in vivo assays that permit 1) repeated, long-term quantitation of angiogenesis and 2) physiological characterization of angiogenic vessels. We report here the development of such an assay in mice. Using this assay, we tested the hypothesis that the physiological properties of angiogenic vessels governed by the microenvironment and vessel origin rather than the initial angiogenic stimulus. Gels containing basic fibroblast growth factor (bFGF) or vascular endothelial growth (VEGF) were implanted in transparent windows in the dorsal skin or cranium of mice. Vessels could be continuously and non-invasively monitored and easily quantified for more than 5 weeks after gel implantation. Newly formed vessels were first visible on day 4 in the cranial window and day 10 in the dorsal skinfold chamber, respectively. The number of vessels was dependent on the dose of bFGF and VEGF. At 3000 ng/ml, bFGF- and VEGF-induced blood vessels had similar diameters, red blood cell velocities, and microvascular permeability to albumin. However, red blood cell velocities and microvascular permeability to albumin were higher in the cranial window than in the dorsal skinfold chamber. Leukocyte-endothelial interaction was nearly zero in both sites. Thus, newly grown microvessels resembled vessels of granulation and neoplastic tissue in many aspects. Their physiological properties were mainly determined by the microenvironment, whereas the initial angiogenic response was stimulated by growth factors.